The Effect of Discounts, Free Shipping, Online Customer Reviews on Purchasing Decisions at the Shopee Marketplace (Case Study on Students of Universitas Muhammadiyah Bengkulu) - Resa Yestasari; Mimi Kurnia Nengsih (Journal of Indonesian Management, 2024)
This research aims to determine "The Influence of Discounts, Free Shipping, Online Customer Reviews on Buying Decisions at the Shopee Marketplace (Case Study of Muhammadiyah University Bengkulu Students)". This type of research is quantitative research, research on measuring data and object statistics through calculations. The population in this study were students at Muhammadiyah University of Bengkulu. The sampling technique was carried out using non-probability sampling, so the total sample in this study was 96 respondents, but for convenience in this study it was rounded up to 100 respondents. Based on the results of the t test, it can be seen that the calculated t for the Discount variable is 5,597 greater than the t table of 1,660 with the probability of t being sig 0.00, which is smaller than the significance limit of 0.05. Based on this value, the Discount variable has a positive effect on the Buying Decision variable. In the Free Shipping variable the calculated t test value is 2.861 which is greater than the t table of 1.660 with a t probability of sig 0.005 which is smaller than the significance limit of 0.05. In the Online Customer Review variable the calculated t value of 8.276 is greater than the t table of 1.660 with a probability t, namely sig 0.00, is smaller than the significance limit of 0.05. Based on the results of the F test, the calculated F value is 35,622 > 2.70 with sig 0.00 < 0.05, Ha is accepted, meaning that Discount, Free Shipping, Online Customer Review simultaneously have a positive and significant effect on the Buying Decision variable. The R Square value obtained was 0.527. To see the magnitude of the influence of the independent variable on the dependent variable by calculating the coefficient of determination (KD) = R2 x 100%, to obtain KD = 52.7%. This figure shows that 52.7% of Buying Decisions (dependent variable) can be explained by discounts, free shipping, and online customer reviews. The remaining 47.3% was influenced by other factors not explained in this study.